Public perceptions of cancer: a qualitative study of the balance of positive and negative beliefs. Issue 7 (10th July 2014) - Robb, Kathryn A; Simon, Alice E; Miles, Anne; Wardle, Jane
Abstract : Objectives: Cancer's insidious onset and potentially devastating outcomes have made it one of the most feared diseases of the 20th century. However, advances in early diagnosis and treatment mean that death rates are declining, and there are more than 30 million cancer survivors worldwide. This might be expected to result in more sanguine attitudes to the disease. The present study used a qualitative methodology to provide an in-depth exploration of attitudes to cancer and describes the balance of negative and positive perspectives. Design: A qualitative study using semistructured interviews with thematic analysis. Setting: A university in London, UK. Participants: 30 participants (23–73 years), never themselves diagnosed with cancer. Results: Accounts of cancer consistently incorporated negative and positive views. In almost all respondents, the first response identified fear, trauma or death. However, this was followed—sometimes within the same sentence—by acknowledgement that improvements in treatment mean that many patients can survive cancer and may even resume a normal life. Some respondents spontaneously reflected on the contradictions, describing their first response as a 'gut feeling' and the second as a more rational appraisal—albeit one they struggled to believe. Others switched perspective without apparent awareness. Conclusions: People appear to be 'in two minds' about cancer. A rapid, intuitive sense of dread and imminent death coexists with a deliberative, rational recognition that cancer can be a manageable, or even curable, disease. Recognising cancer's public image could help in the design of effective cancer control messages.